How to improve the immune system naturally in Pandemi COVID-19? - Hikayati (Conferences of Medical Sciences Dies Natalis, 2020)
Covid-19 has become a world pandemic. In indonesia, surveillance data until october 2020 reported that the average incidence of covid-19 was 3,978 new cases per day in 502 districts from 34 provinces (who, 2020). About 80% of cases with mild symptoms can recover without special treatment, but not all covid-19 patients show signs and symptoms, this is thought to be influenced by the strength of the individual's immune system. Patients who have comorbidities such as diabetes, heart disease, hypertension, pulmonary disease and other chronic diseases will worsen the condition of the immune system. As it is known that the disease caused by the corona virus is a self-limiting disease that will heal itself with a good immune system. Immunity are all mechanisms that the body uses to protect against invading foreign substances or pathogens through an immune response mechanism which is divided into 2 phases : natural immune response (innate immunity) and adaptive immunity. Several ways can be done to improve the imune system. Natural immunity utilizes spices and herbal ingredients which are indonesia's natural resources, as immunomodulators. This is based on several research results and evidence based. Apart from easy manufacturing methods, these ingredients are very easy to find around our environment.